Enhancing Interest in Network Installation with Android-Based Learning for Vocational IT Students - Amrullah, Muhammad Shalahuddin; Gunawan Irianto, Wahyu Sakti (Universitas Negeri Malang, 2023)
This research aims to develop an Android-based learning media called JaringanPedia to increase students' interest in learning about Network Device Installation and Configuration at the Vocational High School level. This media was developed using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The results of the media feasibility analysis show a positive outcome, with a validation value of 92.11 percent from media experts and 86.46 percent from material experts. The media was also tested on students, with a validity score of 85.94 percent for small-scale testing and 86.15 percent for large-scale testing, both categorized as